2014
DOI: 10.1227/neu.0000000000000190
|View full text |Cite
|
Sign up to set email alerts
|

The Volumetric Response of Brain Metastases After Stereotactic Radiosurgery and Its Post-treatment Implications

Abstract: Significant volume reductions of brain metastases measured at either 6 or 12 weeks post-SRS were strongly associated with prolonged local control. Furthermore, early volume reduction was associated with less corticosteroid use and stable neurological symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
2
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 20 publications
3
35
2
9
Order By: Relevance
“…In the present series, a decrease in TV by more than half between the two sessions was the sole factor predicting a high local tumor control rate for large BM. This observation is consistent with the results recently reported by Sharpton et al [28] and appears to be both clinically rational and relevant.…”
Section: Discussionsupporting
confidence: 93%
“…In the present series, a decrease in TV by more than half between the two sessions was the sole factor predicting a high local tumor control rate for large BM. This observation is consistent with the results recently reported by Sharpton et al [28] and appears to be both clinically rational and relevant.…”
Section: Discussionsupporting
confidence: 93%
“…6 There is a paucity of data regarding the tumour response in the early period (<1 month) after stereotac-tic irradiation, even during FSRT, although the regression patterns 1-6 months after single-session radiosurgery have been described. 15,16 In this study, significant TDD was observed in 4 of 21 lesions over a period of 6-13 days (median 7.5 days) until the completion of planned FSRT, for all of which FSRT was Gross tumour volumes (GTVs) before and during treatment are contoured in the lower column as blue and yellow lines, respectively. In the image during treatment, the GTV contour before treatment is also shown for comparison.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, we recognize our use of the early lesional response as a surrogate for treatment efficacy has limitations. Although some studies have suggested that a significant early lesional response to SRS translates into prolonged local control, ultimately, our results still need to be correlated with more traditional measures of clinical outcomes. Future studies could also examine the treatment response on the basis of changes in other magnetic resonance sequences and look at tumor hemorrhage, vascularity, cellularity, or perilesional edema.…”
Section: Discussionmentioning
confidence: 93%